Moisture-absorption-resistant anti-aging nitrocellulose-based water-based coating system as well as preparation method and application thereof
Through the combination of solvent replacement method and epoxy soybean oil, the problem of emulsifier use in the preparation process of the aqueous nitrocellulose coating system in the prior art was solved, and the preparation of the aqueous nitrocellulose coating system with small particle size, uniform distribution, excellent moisture absorption resistance and anti-aging properties was achieved.
Patent Information
- Application Number
- CN202411920287.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-based coating system for nitrocellulose requires emulsifiers and complex emulsification processes during the preparation process, resulting in large particle sizes, uneven distribution, and poor storage stability and water resistance.
The solvent replacement method is used to combine epoxy soybean oil, and the organic solvent is removed by mechanical stirring and rotary evaporation to prepare an aqueous coating system for nitrocellulose, avoiding the use of emulsifiers.
The obtained nitrocellulose aqueous coating system has smaller particles and more uniform distribution. The film has excellent moisture absorption and anti-aging properties, and is suitable for industrial applications.
Smart Images

Figure HDA0005207798590000011 
Figure HDA0005207798590000012 
Figure HDA0005207798590000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nitrocellulose aqueous coating system. Background Art
[0002] Nitrocellulose (NC) is a non-toxic, biodegradable polymer material made by esterifying cellulose with nitric acid. As a film-forming material, NC has the advantages of good mechanical properties, good biocompatibility, strong adhesion, wear resistance, and good gloss. It is widely used in different industries such as printing, packaging, wood coatings, electronic component protective coatings, and medical treatment. However, there are a large number of organic solvents and VOCs (volatile organic solvents) in traditional nitrocellulose lacquer. With the enhancement of environmental protection and safety awareness, it has gradually been replaced by low-pollution, non-flammable nitrocellulose water-based coating system (WNC). At the same time, compared with nitrocellulose lacquer, WNC also has the advantages of high molecular weight, low viscosity, non-flammability, odorlessness, and easy cleaning.
[0003] The inventors found that some work had been done by predecessors in the preparation of WNC dispersions. For example, Shi Hongyue et al. prepared NC aqueous dispersions by direct emulsification, and studied the effects of preparation parameters such as the type, content, and mechanical stirring intensity of emulsifiers on product performance, and obtained NC aqueous dispersions with bright film formation and softness. The direct emulsification method is simple in principle and easy to operate, but the added emulsifier content is large, the prepared particles have large particle size and uneven distribution, and the storage stability of the aqueous dispersion and the water resistance of the film are poor. Bao Huichuan et al. conducted a detailed study on the process of preparing NC aqueous dispersions by phase inversion emulsification and achieved certain research results. Compared with the direct emulsification method, the aqueous dispersion prepared by the phase inversion emulsification method has a smaller particle size, a more uniform size distribution, and a better storage stability of the aqueous dispersion. However, this method has high requirements for emulsifiers, auxiliary plasticizers, and resins, making it difficult to achieve large-scale production and preparation, and the presence of a large amount of emulsifiers also affects the water resistance of the product. Su et al. used the self-emulsification method to introduce hydrophilic groups (carboxyl groups) into the nitrocellulose molecular chain, so that it spontaneously formed WNC with stable thermodynamic properties in the aqueous phase; the WNC prepared by this method has a small particle size and is evenly distributed; but the film formed by drying the WNC contains more hydrophilic groups, and has poor water resistance and tensile properties; on the other hand, the preparation process of this method is complicated and difficult to achieve true industrial application. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the present invention discloses a method for preparing a moisture-absorbing and anti-aging nitrocellulose-based aqueous coating system which does not require the participation of an emulsifier and a complex emulsification process. The solvent replacement method is combined with epoxidized soybean oil to achieve rapid and simple preparation of the nitrocellulose aqueous coating system. The obtained latex particles have smaller particle size and more uniform distribution. At the same time, the formed film has excellent moisture absorption resistance and anti-aging effects, which is convenient for realizing real industrial applications.
[0005] The above technical purpose of the present invention relates to the following technical scheme: a method for preparing a moisture-absorbing and anti-aging nitrocellulose-based aqueous coating system by solvent replacement, wherein nitrocellulose and epoxidized soybean oil are dissolved in a mixed solution of ethanol and acetone to obtain solution one; at a certain temperature, with the assistance of continuous mechanical stirring, the prepared solution one is added to deionized water, and then the solvent is driven off by rotary evaporation to obtain the nitrocellulose aqueous coating system.
[0006] The method comprises the following steps: 1) Dissolve nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone at a mass ratio of 1.0:0.9-1.0:1.0 to prepare a solution 1 with a nitrocellulose concentration of 10-20 mg / mL; 2) Under continuous mechanical stirring, the prepared solution is added into deionized water, and the oil-water mixture is continuously stirred to obtain a milky white and blue-light crude emulsion; 3) removing the organic solvent from the prepared crude emulsion under reduced pressure to prepare an aqueous nitrocellulose coating system having a nitrocellulose solid content of 2% to 16%.
[0007] In step 1, the nitrogen content of nitrocellulose is 11.74-12.2%, and the number average molecular weight is 10000-13300.
[0008] In step 1, the volume ratio of ethanol to acetone in the mixed solution of ethanol and acetone is 8.0:2.0~6.0:4.0.
[0009] Step 2 is specifically as follows: at a temperature of 28±1°C, under continuous mechanical stirring at 300~500 rpm, the prepared nitrocellulose solution is added to deionized water with a volume ratio of 2.0:1.0~1.0:1.0, and the oil-water mixed phase is continuously stirred at 300~500 rpm for 15~30 min to obtain a milky white crude emulsion with a blue glow.
[0010] Step 3 is specifically as follows: adding the prepared crude emulsion into a rotary evaporation bottle, removing the organic solvent in the crude emulsion with a rotary evaporator under reduced pressure conditions of 35-40° C. and 0.098-0.01 MPa, and preparing a nitrocellulose aqueous coating system with a nitrocellulose solid content of 2%-16%.
[0011] On the other hand, the present invention provides a moisture absorption and anti-aging nitrocellulose-based aqueous coating system, which is prepared by the following method: dissolving nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone to obtain solution one; at a certain temperature, with the assistance of continuous mechanical stirring, adding the prepared solution one into deionized water, and then removing the solvent by rotary evaporation to obtain the nitrocellulose aqueous coating system.
[0012] The nitrogen content of the nitrocellulose is 11.74-12.2%, and the number average molecular weight is 10000-13300.
[0013] Another aspect of the present invention provides an application of the above-mentioned moisture absorption and aging resistant nitrocellulose-based aqueous coating system in surface protection and packaging in the fields of cosmetics and food.
[0014] Compared with the prior art, the present invention has at least the following advantages: the preparation of the nitrocellulose-based aqueous coating system by the present invention does not require the participation of an emulsifier, and with the auxiliary effect of the environmentally friendly plasticizer epoxidized soybean oil ESO, it has very good film-forming properties, excellent moisture absorption resistance and aging resistance. The nitrocellulose aqueous coating system prepared by the present invention only contains nitrocellulose and epoxidized soybean oil with excellent biocompatibility, and has low overall production costs and good environmental friendliness, meeting the current trend of green chemistry development. The present invention prepares a nitrocellulose-based aqueous coating system by a solvent replacement method without using any emulsifier, and the film obtained after drying has excellent moisture absorption resistance and aging resistance. It solves the problems existing in the traditional nitrocellulose-based emulsion preparation method, is advanced in replacing the traditional coating system containing organic solvents, and is suitable for surface protection and packaging in the fields of cosmetics, food, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The present invention is a schematic diagram of the process for preparing the moisture absorption and aging resistant nitrocellulose-based aqueous coating system.
[0016] Figure 2 The particle size, PDI and potential value of the aqueous nitrocellulose coating system containing different contents of ESO.
[0017] Figure 3 These are the macroscopic and microscopic morphologies of the films obtained after drying at 60°C with the aqueous nitrocellulose coating system containing ESO with nitrocellulose mass fractions of 60%, 80%, 90%, and 100%.
[0018] Figure 4 The chemical structure of the nitrocellulose aqueous coating system film prepared in Example 2.
[0019] Figure 5 The moisture absorption of the aqueous nitrocellulose coating system film prepared in Example 2 at different relative humidities.
[0020] Figure 6 This is a diagram showing the changes in the chemical structure of the nitrocellulose aqueous coating system film prepared in Example 2 under accelerated aging.
[0021] Figure 7 This is a graph showing the quality change of the nitrocellulose aqueous coating system film prepared in Example 2 under accelerated aging. DETAILED DESCRIPTION
[0022] The technical solution provided by the present invention is described in detail below in conjunction with embodiments. It should be understood that the following specific implementation methods are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0023] Comparative Example 1: Preparation of nitrocellulose aqueous coating system (mass fraction of epoxidized soybean oil 37.5%), the steps are as follows: (1) Dissolve 200 mg of nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone in a volume ratio of 6.0:4.0 at a mass ratio of 5.0:3.0 to prepare 10 ml of nitrocellulose with a concentration of 20 mg mL -1 Clear, homogeneous solution.
[0024] (2) At a temperature of 28±1°C and mechanical stirring at 500 rpm, add 10 mL of the prepared nitrocellulose solution into 10 mL of deionized water. The oil-water mixture is stirred for 15 min to obtain a milky white crude emulsion with a blue luster.
[0025] (3) The prepared crude emulsion was added into a 100 mL rotary evaporation bottle, and the organic solvent in the crude emulsion was removed by a rotary evaporator under reduced pressure conditions (40°C, -0.098 MPa) to prepare a nitrocellulose-based aqueous coating system with a nitrocellulose solid content of 8%, which was named NCE (aqueous phase).
[0026] (4) 5 g of an aqueous coating system with a solid content of 8% nitrocellulose was spread into a polytetrafluoroethylene mold with a diameter of 60 mm and dried in a forced air oven at 60 °C to obtain a nitrocellulose film. The prepared sample was named NCE (solid phase).
[0027] The surface morphology of the film was observed by scanning electron microscopy, and the surface of the sample was treated by gold spraying. Figure 3 As shown, when the content of plasticizer ESO is 60% of the mass of NC, the obtained film still has a large number of cracks in the macroscopic view and has no use value.
[0028] Comparative Example 2: Preparation of aqueous nitrocellulose coating system (mass fraction of epoxidized soybean oil 44.4%) (1) Dissolve 200 mg of nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone in a volume ratio of 6.0:4.0 at a mass ratio of 5.0:4.0 to prepare 10 ml of nitrocellulose with a concentration of 20 mg mL -1 Clear, homogeneous solution.
[0029] (2) At a temperature of 28±1°C and mechanical stirring at 500 rpm, add 10 mL of the prepared nitrocellulose solution into 10 mL of deionized water. The oil-water mixture is stirred for 15 min to obtain a milky white crude emulsion with a blue luster.
[0030] (3) The prepared crude emulsion was added into a 100 mL rotary evaporation bottle, and the organic solvent in the crude emulsion was removed by a rotary evaporator under reduced pressure conditions (40°C, -0.098 MPa) to prepare a nitrocellulose-based aqueous coating system with a nitrocellulose solid content of 8%.
[0031] (4) 5 g of an aqueous coating system with a solid content of 8% nitrocellulose was spread into a polytetrafluoroethylene mold with a diameter of 60 mm and dried in a forced air oven at 60 °C to obtain a nitrocellulose film. The prepared sample was named NCE.
[0032] The surface morphology of the film was observed by scanning electron microscopy, and the surface of the sample was treated by gold spraying. Figure 3 As shown, when the content of plasticizer ESO is 80% of the mass of NC, the number of cracks in the obtained film is reduced macroscopically, but it is still incomplete and also has no use value.
[0033] Example 1: Preparation of aqueous nitrocellulose coating system (mass fraction of epoxidized soybean oil is 47.4%) (1) Dissolve 200 mg of nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone in a volume ratio of 6.0:4.0 at a mass ratio of 5.0:4.5 to prepare 10 ml of nitrocellulose with a concentration of 20 mg mL -1 Clear, homogeneous solution.
[0034] (2) At a temperature of 28±1°C and mechanical stirring at 500 rpm, add 10 mL of the prepared nitrocellulose solution into 10 mL of deionized water. The oil-water mixture is stirred for 15 min to obtain a milky white crude emulsion with a blue luster.
[0035] (3) The prepared crude emulsion was added into a 100 mL rotary evaporation bottle, and the organic solvent in the crude emulsion was removed by a rotary evaporator under reduced pressure conditions (40°C, -0.098 MPa) to prepare a nitrocellulose-based aqueous coating system with a nitrocellulose solid content of 8%.
[0036] (4) Spread 5 g of an aqueous coating system with a solid content of 8% nitrocellulose into a polytetrafluoroethylene mold with a diameter of 60 mm, and dry it in a blast oven at 60°C to obtain a nitrocellulose film. The surface morphology of the film was observed using a scanning electron microscope, and the surface of the sample was treated with gold spraying. Figure 3 As shown, the film is complete, dense, continuous and transparent.
[0037] Example 2: Preparation of aqueous nitrocellulose coating system (mass fraction of epoxidized soybean oil is 50%) (1) Dissolve 200 mg of nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone in a volume ratio of 6.0:4.0 at a mass ratio of 1.0:1.0 to prepare 10 ml of nitrocellulose with a concentration of 20 mg mL -1 Clear, homogeneous solution.
[0038] (2) At a temperature of 28±1°C and mechanical stirring at 500 rpm, add 10 mL of the prepared nitrocellulose solution into 10 mL of deionized water. The oil-water mixture is stirred for 15 min to obtain a milky white crude emulsion with a blue luster.
[0039] (3) The prepared crude emulsion was added into a 100 mL rotary evaporation bottle, and the organic solvent in the crude emulsion was removed by a rotary evaporator under reduced pressure conditions (40°C, -0.098 MPa) to prepare a nitrocellulose-based aqueous coating system with a nitrocellulose solid content of 8%.
[0040] (4) 5 g of an aqueous coating system with a solid content of 8% nitrocellulose was spread into a polytetrafluoroethylene mold with a diameter of 60 mm and dried in a forced air oven at 60°C to obtain a nitrocellulose film. The prepared sample was named NCE. The thickness of the film was measured by a spiral micrometer and was 0.2 mm.
[0041] The characteristic tests of the aqueous nitrocellulose coating system include the particle size distribution and stability of the nanoparticles contained in the coating system, the microstructure of the film made of the coating system, Fourier transform infrared spectroscopy, thermal stability, hygroscopicity, and long-term storage stability analysis.
[0042] Characterization of particle size, PDI and potential value in the aqueous nitrocellulose coating system obtained in step 3: The average particle size (Zave), polydispersity index (PDI) and zeta potential of the aqueous nitrocellulose coating system were measured by dynamic light scattering method using a nanoparticle size potential analyzer. All measurements were performed at a temperature of 25.0±0.1℃ and repeated at least three times. Figure 2 The particle size, PDI and potential value diagram of the aqueous nitrocellulose coating system without ESO and the aqueous nitrocellulose coating system with ESO added at a mass ratio of 1:1 to NC are shown in Figure 2. Figure 2 As shown, the addition of ESO leads to an increase in the size of NC aqueous dispersion, and the size of the aqueous dispersion increases from 98.05 nm (NC:ESO=1.0:0.0 (w / w)) to 115.07 nm (NC:ESO=1.0:1.0 (w / w)). The existence of this phenomenon is related to the formation mechanism of NC aqueous dispersion. Since ESO is an oil-soluble plasticizer, it has good affinity for ethanol and acetone. When it is mixed with NC solution and added to the aqueous phase, it will slow down the diffusion process of organic solvent into the aqueous phase, thereby prolonging the time for NC solution to reach supersaturation, resulting in an increase in the particle size of the final particles. At the same time, as a plasticizer, ESO has good plasticizing and dissolving ability for NC. Therefore, when it is added to the NC organic solution, the dissolving ability of the mixed solvent for NC will be improved, further delaying the rate at which the NC mixed solution reaches supersaturation, which will also cause the size of NC nanoparticles to increase. In addition, ESO is insoluble in water. After the nanoparticles are formed, it exists inside the formed NC nanoparticles, which will also increase the volume of the particles. In addition, the potential value of the NC aqueous dispersion did not change significantly with the addition of ESO plasticizer, and remained at about -30 mV. This shows that the presence of the plasticizer did not destroy the good stability of the NC aqueous dispersion. After adding the plasticizer, the PDI value of the NC aqueous dispersion fluctuates to a certain extent, because the addition of the plasticizer delays the process of the NC solution reaching a supersaturated state, thereby causing the particle size dispersity of the NC aqueous dispersion to fluctuate. In general, the nitrocellulose aqueous coating system prepared by the present invention has good particle size distribution and storage stability.
[0043] Microstructure analysis of the nitrocellulose aqueous coating system film obtained in step 4: The surface morphology of films containing different contents of ESO was observed by scanning electron microscopy, and the surface of the samples was treated by gold spraying.
[0044] like Figure 3 As shown in the figure, when the content of plasticizer ESO is 60% of the mass of NC, the obtained film still has a large number of cracks on a macroscopic scale, but it is transparent as a whole, with only the edges showing white fragments. The film has a certain mechanical strength, and its interior is no longer entirely isolated nanoparticles, but there are more continuous polymer blocks, which indicates that the internal NC nanoparticles have begun to fuse under the action of ESO. As the content of doped ESO increases to 80% of the mass of NC, the number of surface cracks on the prepared film decreases and the integrity of the film improves. When the ESO content is further increased to 90% and 100% of the mass of NC, the film becomes complete, dense, continuous and transparent.
[0045] Fourier transform infrared spectroscopy analysis of the nitrocellulose aqueous coating system film obtained in step 4: The surface chemical structures of NC, ESO and the prepared thin film (NCE) were characterized by Fourier transform infrared spectroscopy (FT-IR), and the interfacial interaction between ESO and NC matrix was analyzed in detail.
[0046] The wave number range of the infrared spectrometer is 4000 cm -1 ~ 550 cm -1 .
[0047] The peak results of infrared spectrum are as follows Figure 4 For NC, 3558 cm -1 The weak absorption characteristic peak near 2970 cm -1 and 2920 cm -1 The absorption peaks near 1633 cm are related to the stretching vibrations of various CH -1 and 1273 cm -1 The characteristic absorption peak at 822 cm is related to the asymmetric and symmetric stretching vibration of -NO2 of the nitrate group in the NC molecular chain. -1 、747 cm -1 and 676 cm -1 The characteristic absorption peak at 1736.15 cm-1 is attributed to the shear vibration, asymmetric and symmetric deformation vibration of -O-NO2. Compared with NC, the alkyl absorption peak intensity of NCE film is significantly enhanced after adding ESO, which is attributed to the stretching vibration of -CH3 and -CH2 in the molecular structure of ESO. -1In addition, compared with NC, the peak of nitrate in NCE has a certain blue shift, while compared with ESO, the peak of carbonyl in NCE film has a significant red shift, indicating that hydrogen bonds may be formed between NC molecules and NCE plasticizer molecules during the film formation process, which shows that ESO and NC have good compatibility.
[0048] Analysis of the hygroscopic properties of the nitrocellulose aqueous coating system film obtained in step 4: The dynamic vapor sorption instrument (DVS) was used to measure and analyze the moisture absorption process of the composite film. ◦ The experiments were carried out at a constant temperature of 1.5 °C and the relative humidity (RH) was increased in 10% increments until 90% RH.
[0049] like Figure 5 As shown in the figure, the saturated moisture content (EMC) value of the NC film increases rapidly at low relative humidity (< 20%); with the increase of relative humidity, the plasticization of the isotherm slows down; when the relative humidity is greater than 80%, the EMC value increases sharply again. After adding ESO plasticizer to the NC aqueous dispersion, it can be found that the hygroscopicity of the NCE film is significantly reduced. At the highest relative humidity (90%), the EMC of NCE is 0.987%, which is much lower than 2.691% of NC. Both plasticizers are commonly used water-insoluble plasticizers with good water resistance.
[0050] The long-term storage stability of the aqueous nitrocellulose coating system film obtained in step 4: A certain amount of NCE film was weighed accurately and placed in a blast oven for accelerated aging at a temperature of 50 °C and a wind speed of 2.5 m·s. -1 Infrared spectroscopy was used for chemical structure analysis, and an electronic balance was used for mass measurement to obtain the aging performance results of the film.
[0051] like Figure 6 and Figure 7 As shown, within 49 days of thermal aging, the chemical structure of the NCE film remained intact and the overall quality remained basically unchanged. It exhibited excellent anti-aging properties and is therefore a potential material that can be used to coat propellants.
[0052] In summary, the present application obtains a nitrocellulose aqueous coating system by combining a solvent replacement method with ESO plasticization. Under the conditions of a relative humidity of 90% and a temperature of 25°C, the saturated moisture absorption of the NCE film is less than 1%, which effectively solves the problem of easy moisture absorption of the traditional nitrocellulose aqueous coating system; at the same time, the NCE film can be stably stored for more than 49 days at 50°C without changes in the physical and chemical structure, and has excellent aging resistance. The present invention utilizes a solvent replacement method, combined with the excellent plasticizing effect of epoxy soybean oil, to prepare a green, environmentally friendly, moisture-resistant and anti-aging nitrocellulose aqueous coating system, expanding the preparation concept in the field of aqueous coating. The method is simple to operate, low-cost, environmentally friendly, and has an adjustable NC content. It avoids the use of emulsifiers and complex emulsification equipment, and solves many problems of traditional preparation methods such as complex operation, serious pollution, and poor product consistency. It has broad application prospects.
[0053] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a moisture absorption and anti-aging nitrocellulose-based aqueous coating system by solvent replacement, characterized in that: The nitrocellulose and epoxidized soybean oil are dissolved in a mixed solution of ethanol and acetone to obtain a solution 1; at a certain temperature, with the assistance of continuous mechanical stirring, the prepared solution 1 is added into deionized water, and then the solvent is driven off by rotary evaporation to obtain a nitrocellulose aqueous coating system.
2. The method for preparing a nitrocellulose-based aqueous coating system resistant to moisture absorption and aging according to claim 1, characterized in that: The method comprises the following steps: 1) Dissolve nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone at a mass ratio of 1.0:0.9-1.0:1.0 to prepare a solution 1 with a nitrocellulose concentration of 10-20 mg / mL; 2) Under continuous mechanical stirring, the prepared solution is added into deionized water, and the oil-water mixture is continuously stirred to obtain a milky white and blue-light crude emulsion; 3) removing the organic solvent from the prepared crude emulsion under reduced pressure to prepare an aqueous nitrocellulose coating system having a nitrocellulose solid content of 2% to 16%.
3. The method for preparing a moisture absorption and aging resistant nitrocellulose-based aqueous coating system according to claim 2, characterized in that: In step 1, the nitrogen content of nitrocellulose is 11.74-12.2%, and the number average molecular weight is 10000-13300.
4. The method for preparing a moisture absorption and aging resistant nitrocellulose-based aqueous coating system according to claim 2, characterized in that: In step 1, the volume ratio of ethanol to acetone in the mixed solution of ethanol and acetone is 8.0:2.0~6.0:4.
0.
5. The method for preparing a moisture absorption and aging resistant nitrocellulose-based aqueous coating system according to claim 2, characterized in that: Step 2 is specifically as follows: at a temperature of 28±1°C, under continuous mechanical stirring at 300~500 rpm, the prepared nitrocellulose solution is added to deionized water with a volume ratio of 2.0:1.0~1.0:1.0, and the oil-water mixed phase is continuously stirred at 300~500 rpm for 15~30 min to obtain a milky white crude emulsion with a blue glow.
6. The method for preparing a moisture absorption and aging resistant nitrocellulose-based aqueous coating system according to claim 2, characterized in that: Step 3 is specifically as follows: adding the prepared crude emulsion into a rotary evaporation bottle, removing the organic solvent in the crude emulsion with a rotary evaporator under reduced pressure conditions of 35-40° C. and 0.098-0.01 MPa, and preparing a nitrocellulose aqueous coating system with a nitrocellulose solid content of 2%-16%.
7. A moisture absorption and anti-aging nitrocellulose-based aqueous coating system, characterized in that: The preparation method is as follows: dissolving nitrocellulose and epoxidized soybean oil in a mixed solution of ethanol and acetone to obtain solution one; at a certain temperature, with the assistance of continuous mechanical stirring, adding the prepared solution one into deionized water, and then removing the solvent by rotary evaporation to obtain the nitrocellulose aqueous coating system.
8. The moisture absorption and aging resistant nitrocellulose-based aqueous coating system according to claim 7, characterized in that: The nitrogen content of the nitrocellulose is 11.74-12.2%, and the number average molecular weight is 10000-13300.
9. Use of the moisture absorption and aging resistant nitrocellulose-based aqueous coating system according to claim 7 or 8 in surface protection and packaging in the field of cosmetics and food.
Citation Information
Patent Citations
Nitrocellulose emulsion for leather and preparation method of nitrocellulose emulsion
CN110343427A
Blended film containing nitrocellulose and plasticizer and preparation method thereof
CN115678110A
Improvements in and relating to aqueous emulsions of nitrocellulose and to processes for manufacturing the same, and to paper products treated with the same
GB499858A